Barium recovery using crystallization in a fluidized-bed reactor - Reaño, Resmond L. (2013)
Environmental crystallization is identified as one of the most efficient and economical method to treat heavy-metal pollutants in soil and water, using a fluidized-bed process. Many anions can be a forerunner that forms sparingly soluble salts with heavy-meta; ions, but only, metal phosphate is of practical importance. The effect of process conditions which include upward velocity inside the column, addition of seed and varying seed size range, pH level of the precipitant or phosphate stream and barium to phosphate (Ba/P) mixing ratio was studied, aimed to produce barium hydrogen phosphate (BaHPO4) crystals of significant size and maximize barium removal, An upward velocity of 48 cm/min produced 0.84 to 1.0 mm BaHPO4 crystals. Addition of seed has no effect on barium removal, while the following sequence of seed size range used: unseeded < 0.149 to 0.29 < less than 0.149 < 0.29 to 0.42 shows increasing amount of larger crystals produced. Maximum size of pure BaHPO4 identified using XRD analysis was attained using pH range of 8.4 to 8.8 with Ba/P equal to1.0. Beyond or less than the given pH range and Ba/P produced finer crystals. 98% barium removal was achieved using the determined condition.